Burkina Faso : Poverty Reduction Strategy Paper Progress Report-Joint Staff Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Despite severe exogenous shocks, the macroeconomic program remained broadly on track, and several social indicators, particularly in the area of basic education, progressed. A variety of measures have been successfully implemented to improve the environment for private sector development, reduce the vulnerability of the rural sector, and strengthen public finance management. A more comprehensive framework for growth-enhancing policies should encompass the rural sector; foster the development of analytical links between budgets and results; and strengthen the role of the Poverty Reduction Strategy Paper (PRSP) as an integrative framework for sectoral policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet